Meta-Analysis the Impact of Technological Advancements on Social Interaction in the Digital Era - Putri, Desly Dwiyana; Andini, Syasya; Ingtyas , Fatma Tresno; Sabrina, Elsa (Journal Corner of Education, Linguistics, and Literature, 2024)
This study aims to analyze the impact of technological advancements on social interactions in the digital era. Using the meta-analysis method, data were collected from 15 relevant journals through a Google Scholar search. The findings reveal that technological advancements, particularly the use of gadgets and social media, have positive impacts, such as expanding social networks and facilitating communication. However, negative impacts were also identified, including a decline in the quality of social relationships due to reduced face-to-face interactions, increased social isolation, and various health issues. This study provides recommendations for the wise use of technology, such as through digital education and limiting gadget usage, to balance the benefits of technology with the quality of social relationships.